Effective functionalization of porous polymer fillers to enhance CO2/N2 separation performance of mixed-matrix membranes - Lee, Y. (Elsevier B.V., 2022)
A series of porous organic polymers (denoted as PBP-x) possessing various functional groups was synthesized via FriedelâCrafts alkylation followed by post-synthetic functionalization using amine and sulfonic groups. These functionalized porous polymers were incorporated into an in-house polyimide to fabricate mixed-matrix membranes for CO2/N2 separation. Gas permeation testing revealed that these functionalized porous fillers substantially improved the CO2 separation performance. Moreover, optimizing both the functionality and pore structure of the porous fillers was found to drastically improve the CO2/N2 separation performance. In particular, the addition of 10 wt PBP-menm (menm = 1,2-methylethylenediamine) induced an ultrahigh CO2 permeability of 2988 barrers (158 higher than that of a pure polymer membrane), thus realizing excellent performance that surpasses the Robeson upper bound for CO2/N2 separation. Â© 2022 Elsevier B.V.